Isothermal and anisothermal creep behavior of the nickel base Alloy 602 CA. Issue 2 (17th February 2021) - Schwing, R.; Linn, S.; Kontermann, C.; Neubert, S.; Oechsner, M.
Abstract: Components in industrial furnaces and apparatus construction are usually exposed to temperatures up to 1, 200 °C as well as mechanical loading and corrosive attack of the environmental atmosphere. Furthermore, they undergo numerous temperature cycles in service. To describe the characteristics of the nickel base Alloy 602 CA, which is often used in this industrial sector, the long term creep behavior of this alloy was studied at temperatures from 800 °C to 1, 200 °C with and without thermal cycling. During these tests unexpected effects could be noticed. At load levels representing typical component loads and isothermal temperature control an anomalous decrease in creep rate in the third creep stage was observed. Experiments under thermal cycling showed a considerably higher creep rate in the whole range than in the isothermal case. Within the present article, these findings are outlined in detail together with a brief discussion of causes and consequences based on extensive microstructural examinations. Abstract : In this paper, a systematic examination of the creep behavior of the material Alloy 602 CA and resulting unexpected effects will be discussed. Findings and approaches will be outlined to clarify the phenomena of an unusual decrease in creep rate within the tertiary creep regime under isothermal conditions as well as the effect of an increased creep rate under anisothermal conditions. Translation abstract: Bauteile im industriellen Ofen‐ und Apparatebau sind Temperaturen bis über 1.200 °C sowie mechanischer Beanspruchung und korrosivem Angriff durch die Umgebungsatmosphäre ausgesetzt. Außerdem kommt es während des Betriebs zu zahlreichen Temperaturwechseln. Um die Eigenschaften der Nickelbasislegierung Alloy 602 CA unter diesen Bedingungen zu beschreiben, wurde das langzeitige Kriechverhalten bei Temperaturen von 800 °C bis 1.200 °C mit und ohne zyklische Temperaturwechselbeanspruchung experimentell untersucht. Bei niedrigen Spannungen und isothermer Versuchsführung wurde hierbei eine ungewöhnliche Abnahme der Dehnrate im tertiären Kriechbereich beobachtet. Unter Temperaturwechselbeanspruchung konnte dagegen eine erheblich höhere Dehnrate im Vergleich zum isothermen Fall festgestellt werden. Die Diskussion der experimentellen Ergebnisse sowie der ergründeten Ursachen auf Basis mikrostruktureller Nachuntersuchungen sind Hauptgegenstände des vorliegenden Beitrags.